Perilaku Belajar Peserta Didik Pasca Pembelajaran Daring di SMAN 4 Pariaman - Fira Yanda Putri; Eka Asih Febriani (Jurnal Sikola: Jurnal Kajian Pendidikan dan Pembelajaran, 2022)
The background of the research is the phenomenon of student learning behavior after online learning at SMAN 4 Pariaman. In the 2021/2022 academic year, online learning is shifted to face-to-face learning, resulting in changes in student learning behavior. The purpose of this study is to describe the form of student learning behavior after online learning. The theory used in this research is the behavioristic learning theory of B.F Skinner. This research method is qualitative with a case study type. The informant selection technique used is the purposive sampling technique. The number of informants in this study was 13 people consisting of students, sociology teachers, and parents of students. Data were collected through observation, interviews, and documentation. Data analysis used Miles and Huberman's interactive data analysis, which consisted of data collection, data reduction, data presentation, and conclusion. The results obtained are the form of student behavior after online learning, namely often arriving late to school but being willing to participate in group discussions, completing assignments on time, using textbooks as learning resources, being enthusiastic in completing daily tests, and being willing to repeat lessons at home.